Development of a Cost-Effective and High-Efficiency Incubator for Small-Scale Poultry Farmers to Maximize Hatchability and Brood Quality (Indian Journal of Animal Production and Management, 2024)
Today, small-scale poultry farming plays a  significant role in meeting the global demand for  poultry products. It is no secret that small-scale  farmers' profitability is strongly impacted by the  effectiveness of egg incubation, a key stage in  poultry production. Brood quality and hatchability  are strongly affected by temperature, humidity,  ventilation, and turning during the incubation stage.  Considering all these factors, designing an  accurate, affordable, and effective incubator has  become a challenging task. Incubation systems are  now widely used by large-scale chicken farmers but  small-scale poultry producers do not employ them  as frequently. The lack of finance and technology  has hindered the efforts of numerous small-scale  chicken farmers who have expressed interest in  employing incubation systems. Taking all these  factors into consideration, this research has  developed a highly efficient and cost-effective egg  incubator that satisfies the special needs of small scale poultry farmers to solve those problems. The  results of this study showed remarkable efficiency  of up to 90% with a high yield of eggs stored in the  compact incubator by maintaining optimal  conditions of temperature, humidity, ventilation, egg  turning, and other critical factors. In addition, this  creative approach can contribute more to the  growth of small-scale farmers' economy and to  meet the global demand for poultry products.
Keywords: egg incubator; hatching time; poultry production; small-scale farmers